2021
DOI: 10.21608/jcvr.2021.199440
|View full text |Cite
|
Sign up to set email alerts
|

Potential Toxic Effects of Aluminum Nanoparticles: An overview

Abstract: Alumina (aluminum oxide) nanoparticles (AlNPs) have been categorized among the most important nano-metals, with wide applications in many fields as in food, agriculture, industry, engineering, pharmacy, medicine and others. The extensive use of AlNPs results in a massive release of them into the environment resulting in potential adverse impacts on animals and human health. Toxicokinetic studies demonstrated the rapid absorption and the systemic distribution of AlNPs to different organs. AlNPs mainly induced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Nevertheless, Al 2 O 3 NPs have been reported to cause the release of reactive oxygen species (ROS), DNA mutations, and pro-inflammatory cytokines, which cause significant damage to the kidneys, brain, liver, and immune system [ 14 ]. Recently, in vitro and in vivo studies have revealed that Al 2 O 3 NPs have hepatotoxicity, nephrotoxicity, myocardial toxicity, reproductive toxicity, and neurotoxicity effects [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, Al 2 O 3 NPs have been reported to cause the release of reactive oxygen species (ROS), DNA mutations, and pro-inflammatory cytokines, which cause significant damage to the kidneys, brain, liver, and immune system [ 14 ]. Recently, in vitro and in vivo studies have revealed that Al 2 O 3 NPs have hepatotoxicity, nephrotoxicity, myocardial toxicity, reproductive toxicity, and neurotoxicity effects [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cellular accumulation of Al 2 O 3 NPs resulted in interaction with cell components and binding with proteins and nucleic acids producing cellular oxidative damage. Also, cell death was caused by Al 2 O 3 NPs due to their ability to compromise mitochondrial membranes, deplete mitochondrial thiols, activate apoptotic caspases (9 and 3), and increase ROS production (Alshatwi et al 2013 ; Elkhadrawy et al 2021 ). Additionally, Liu et al ( 2020 ) stated that Al 2 O 3 NPs toxicity induced apoptosis; subsequently, the expression of BCL-2, cyclin D1, Mdm2, and phospho-Rb was decreased and that of p53, Bax, p21, and Rb was increased.…”
Section: Discussionmentioning
confidence: 99%
“…Al NPs can act neurodegenerative, [ 35 ] while its oxide compound intracellularly up taken as Al 2 O 3 [ 36 ] can interfere with intracellular proteins, genomic deoxyribonucleic acid (DNA), and messenger ribonucleic acids (mRNAs) [ 37 ]. In general, the accumulation of NPs in organs over time can additionally give rise to a systemic, inflammatory response and interfere with the immune system as shown in animal model studies on Au, Ag as well as Al NPs [ 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%